Numerical comparison of sinc-collocation and Chebychev-collocation methods for determining the eigenvalues of Sturm–Liouville problems with parameter-dependent boundary conditions - El-Gamel, Mohamed (SeMA journal, 2014)
In this paper, we will compare the performance of sinc-collocation method and the Chebychev-collocation method applied to determine the eigenvalues of Sturm–Liouville problems with parameter-dependent boundary conditions. The numerical results indicate that the chebychev method possesses a significant computational advantage over the sinc-collocation method.